Climate Variability and Climate Change Impacts on Land Surface, Hydrological Processes and Water Management - Reggiani, Paolo (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
During the last several decades, Earth´s climate has undergone significant changes due to anthropogenic global warming, and feedbacks to the water cycle. Therefore, persistent efforts are required to improve our understanding of hydrological processes and to engage in efficient water management strategies that explicitly consider changing environmental conditions. The twenty-four contributions in this book have broadly addressed topics across four major research areas: (1) Climate and land-use change impacts on hydrological processes, (2) hydrological trends and causality analysis faced in hydrology, (3) hydrological model simulations and predictions, and (4) reviews on water prices and climate extremes. The broad spectrum of international contributions to the Special Issue indicates that climate change impacts on water resources analysis attracts global attention. We hope that the collection of articles presented here can provide scientists, policymakers and stakeholders alike with insights that support sustainable decision-making in the face of climate change and increasingly scarce environmental resources.